Aujeszky’s Disease (Pseudorabies). An old threat in current pig industry? Part II. Epidemiology, Immunity, Prevention and the current situation in Greece - PAPAGEORGIOU (Κ.Β. ΠΑΠΑΓΕΩΡΓΙΟΥ) K. V.; BURRIEL, A. R.; FILIOUSSIS (Γ. ΦΙΛΙΟΥΣΗΣ) G.; CHRISTODOULOPOULOS (Γ. ΧΡΙΣΤΟΔΟΥΛΟΠΟΥΛΟΣ) G.; NAUWYNCK, H. J.; KRITAS (Σ.Κ. ΚΡΗΤΑΣ) S. K. (Journal of the Hellenic Veterinary Medical Society, 2017)
Aujeszky’s disease (AD) (or Pseudorabies) is an important viral disease of swine causing neurological signs in neonatal pigs, respiratory problems in fatteners and reproductive disorders in breeding stock. Swine is the only natural host of Aujeszky’s disease virus (ADV) and the only species that can survive its infection. Its transmission is mainly through nose-to-nose contact, but several other ways may apply. Both antibody- and cell-mediated immune responses occur following ADV infection, while maternal immunity can protect the pigs depending on their level and the virulence of the infecting strain. Virus glycoproteins may, also, play a role in immunity with that of gC and gD being the most important. Prevention and control of ADV is based on proper vaccination and biosecurity measures, while eradication has been practiced in various ways depending on the situation. The current vaccines are based on deletion of certain proteins and are effective. Despite the fact that the disease has been eradicatedfrom many developed countries, AD is still endemic in Greece. Findings of recent emergence of AD in Greek farms and the possibility of its eradication are discussed.